Scripture-Mere Text? - Gerald Bray (STT Reformed Injili Internasional, 2014)
In this article, the writer is responding critically the saying of Benjamin Jowett who assume that the Bible is an ordinary book and should be read as an ordinary book. With historical theological argumentation and dialogue between the tension of sciences, the writer defended that the bible is truly the Word of God and that the Holy Spirit witness within it. Therefore, the Bible cannot be read as an ordinary book.?